Analisis Maṣlaḥah terhadap Surat Edaran Zakat Fitrah dan Fidyah Tahun 2025: Studi Kasus di Kabupaten Sambas - Wiwin Andini; Raharjo Raharjo; Abdul Ghofur (IAIN Langsa, 2026)
This study aims to analyze the aspect of maslahah and the effectiveness of the policy from the perspective of Islamic law. This research employs a qualitative method with a field research approach and descriptive analytical methodology. Primary data are derived from the related circular letter, while secondary data are obtained from relevant scientific literature. Data analysis is conducted through data reduction, data display, and conclusion drawing, with validity ensured through source triangulation. The findings indicate that, conceptually, the policy aligns with the principle of maslahah, particularly in enhancing the welfare of mustahik and reflecting prudence in religious practice. However, in practice, its effectiveness remains suboptimal due to limited socialization, differences in understanding, and variations in community compliance, thus requiring improved policy communication and public education.